Hubungan Pengetahuan dan Sikap terhadap Pola Pemilihan Obat Tradisional untuk Pengobatan Sendiri (Self Medication) pada Masyarakat DesaKalisoro - Hanugrah Ardya Crisdian; Agnes Prawistya; Ersta Zuzvita; Rufaida Nur Fitriana (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2022)
Self medication is the use of drugs by the public to reduce the symptomps of minor illnesses without a doctor’s advice. Self medication behavior may be influenced by gender, age, education level, employments status, income level and atitudes about self medication. Increased education and awerness of students about helath, the use of drugs for self medication will also increase. This study aims to identify the reklationship between knowledge anattitudes toward the pattern of using traditional medcine in the Kalisoro village. This research ia an observasional study with a cross sectional reseacrh design. The sampling thecnique was non- random sampling. Collecting data using a quistionnaire, Ehich has been tasted for validity and realibily. Data analysis was carried out using two methods, namely descriptive sattistical methods in the fgorm of respondents charateristic, knowledge, attitude and patterns, while correlation using the Eta Correlation Cooeficient. Inthis study there were many as 60 respondents who participated, with high level of knowledge as many as 95% of respondents who have positive attitude or partially. There is very low or very weak relationship in terms of knowledge, while in attitude there is a high or strong relation ship with each pattern of traditional medcine use which includes the frequency of use traditional medcines used, drug prices and sources of information.